Energy and exergy analysis of solar stills by using single and hybrid nanofluid and experimentally determined climatic conditions - Selimefendigil, Fatih; Cakmak, Fethi Ahmet; Öztop, Hakan Fehmi (Inderscience Enterprises Ltd, 2026)
In this study, the performance improvement of solar stills using different nanofluids was investigated analytically. Addition of CNTs to water (case 1), addition of Cu-Al2O3 nanoparticles (case 2) and addition of Al2O3-MWCNT-graphene nanoparticles (case 3) were considered. By using binary nanofluid, 26.67% more water was obtained compared to the traditional distiller. Similarly, a 24.41% energy efficiency and 33.32% increase in exergy efficiency was achieved. Outcomes is useful for selection of appropriate hybrid nanoparticles in nano-enhanced solar stills as hybrid nanofluids in energy systems is considered due to the cost, stability and synergistic impacts of individual nanoparticles on the overall performance.
Keywords: energy efficiency; nanofluid; nanoparticle; solar still; heat transfer